Study on dynamic characteristics of activated products source term in secondary loop of integrated molten salt reactor. (June 2020) - Zhou, Bo; Yu, Xiao-Han; Liu, Ya-Fen; Zou, Yang; Yang, Pu; Yu, Shi-He; Kang, Xu-Zhong; Zhu, Gui-Feng; Yan, Rui
Abstract: Source term analysis not only can provide the fundamental data for radiation shielding design, but also has a guiding significance for in-service inspection of the reactor. A numerical analysis model (MAST1.0) for activated products in the secondary loop system of the molten salt reactor (MSR) was developed. The deviation of the simulation results between MAST1.0 and ORIGEN-S are less than 7%, which indicates that they are in good agreements. The amounts of the activated products ( 16 N, 20 F and 19 O) and the corrosion activated products ( 60 Co, 55 Fe, 54 Mn, 51 Cr, 59 Ni, etc.) in the second loop were also obtained by MAST1.0, which show that the total activity of 16 N, 20 F and 19 O is two orders of magnitude higher than that of the corrosion activated products in normal operating conditions. Flow rate has a significant effect on the distribution of 16 N, 20 F and 19 O in the secondary loop. The total activity of 16 N, 20 F and 19 O outside of the core increases monotonically with the increase of the flow rate. The concentration of 16 N, 20 F and 19 O outside of the core tends to be stable, when the flow rate is greater than 1 × 10 6 cm 3 s −1 . Corrosion activated products show slowly increasing and decreasing trends in reactor startup and shutdown conditions, so they are the key radioactive sources for radiation protection after long-term shutdown of the reactor. Highlights: Source term of activation products is key shielding design source term. MAST1.0 was developed for activated products calculation for the MSR secondary loop system. Results obtained by MAST1.0 are in good agreement with that by ORIGEN-S. Flow rate has a significant effect on the distribution of 16 N, 20 F and 19 O in the secondary loop. Corrosion activated products are the key radioactive sources after long-term shutdown of MSRs.